A novel human cDNA with a predicted protein similar to lysyl oxidase maps to chromosome 15q24-q25 - Kenyon, K.; Modi, W.S.; Contente, S.; Friedman, R.M. (The Journal of biological chemistry, 1993)
A novel human cDNA with a predicted protein homologous to the carboxyl end of lysyl oxidase, an extracellular enzyme involved in the maturation of collagen and elastin, has been isolated. The homology to lysyl oxidase begins exactly at the position of the exon 1/exon 2 boundary in the mouse gene (Contente, S., Csiszar, K., Kenyon, K., and Friedman, R. M. (1993) Genomics 16, 395-400). This lysyl oxidase-like gene, which appears to be no larger than 22.1 kilobases, codes for a single polyadenylated RNA species of 2.48 kilobases and has been mapped to chromosome 15q24-q25.